Effectiveness of social capital based community of practice model in entrepreneurship education - Entoh Tohani (LPPM UNY, 2014)
This study aimes to reveal the effectiveness of the social-capital-based community of practice for improving entrepeneurhsip-education quality in the context of community development to hopefully give contributions to the educational theory and practice. Community of practice is a medium for sharing experience and knowledge among people who run entreprises and want their entreprise to grow. It will be more useful if social capital can be used and developed on its management. The study was done by using the research and development (RD) approach. The target subjects were two groups of small-scale businesses chosen purposively. The results of the study show that the CoP model is effective and raises the awareness of the members, so that CoP must be run in their enterprise; have the determination to keep commitment and positive values; build trust and enlarged networking to doers of entreprises; and motivate them to develop their business.